Evaluation of a Medium for the Rapid Recovery of Escherichia coli from Shellfish - Andrews, Wallace H. (1975)
A medium (A-1) which shortens the time necessary to identify and enumerate Escherichia coli found in estuarine water was evaluated for use for recovery of E. coli found in shellfish. Productivity of E. coli by this medium was comparable to that of the lengthier American Public Health Association method, and the occurrence of false positives was substantially reduced.